Evidence for host–microbiome co‐evolution in apple. Issue 6 (25th November 2021) - Abdelfattah, Ahmed; Tack, Ayco J. M.; Wasserman, Birgit; Liu, Jia; Berg, Gabriele; Norelli, John; Droby, Samir; Wisniewski, Michael
Summary: Plants evolved in association with a diverse community of microorganisms. The effect of plant phylogeny and domestication on host–microbiome co‐evolutionary dynamics are poorly understood. Here we examined the effect of domestication and plant lineage on the composition of the endophytic microbiome of 11 Malus species, representing three major groups: domesticated apple ( M .  domestica ), wild apple progenitors, and wild Malus species. The endophytic community of M .  domestica and its wild progenitors showed higher microbial diversity and abundance than wild Malus species. Heirloom and modern cultivars harbored a distinct community composition, though the difference was not significant. A community‐wide Bayesian model revealed that the endophytic microbiome of domesticated apple is an admixture of its wild progenitors, with clear evidence for microbiome introgression, especially for the bacterial community. We observed a significant correlation between the evolutionary distance of Malus species and their microbiome. This study supports co‐evolution between Malus species and their microbiome during domestication. This finding has major implications for future breeding programs and our understanding of the evolution of plants and their microbiomes.